8.0k views
0 votes
Pls answer this question assap

Pls answer this question assap-example-1
User GWorking
by
5.1k points

2 Answers

5 votes

Answer:


y = - (37)/(57)

Explanation:


(9 - 3y)/(1 - 9y) = (8)/(5)


(3(3y - y))/(1 - 9y) = (8)/(5)


3(3−y) * 5=(1−9y) * 8


45−15y=(1−9y) * 8


45−15y=8−72y


45+57y=8


57y=8−45


57y=−37


y = - (37)/(57)

Hope it is helpful....

User Bruno Reis
by
5.3k points
3 votes

Answer:

Explanation:


(9-3y)/(1-9y) = (8)/(5)

do cross multiplication


5(9 - 3y) = 8(1 - 9y)\\45 - 15y = 8 - 72y\\45 - 8 = -72y + 15y\\37 = -57y\\(37)/(-57) = y

User Peter Schott
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.